Students’ Perceptions and Attitudes toward World Englishes Paradigm - Sesmiyanti; Imelwaty, Sri; Rahmi Putri, Yulistia (UNIB Press, 2023)
The study aims to describe the pre-service English teachers’ perceptions and attitudes toward World Englishes (WE) Paradigm from Kachru's theory within the Indonesian context. Limited studies have been undertaken relating to Indonesian pre-service teachers’ perceptions and attitudes to the WE paradigm. The design of this study employed a qualitative case study focusing on the exploration of an individual pre-service English teacher’s perceptions and attitudes toward the phenomenon of the WE paradigm. Twenty participants who are pre-service English teachers participated in this study. Initially, the participants were asked to take The Verbal Guise Test to for stimulating the participants’ knowledge (cognitive) about varieties of English and introduce the WE paradigm. Afterward, the semi-structured interview was conducted with open-ended questions to explore how the students view different varieties of WE. The data were then transcribed and analyzed using thematic analysis by coding, classifying themes, and interpreting. The findings of the study indicated that academically participants still have a preference of the inner circle (IC) English to support the learning process. But for non-academic context the majority of participants had the ability to understand and recognize English variations and showed interest in using and learning more about WE.